Can Meditation Control the Suicidal Thought? - A Spiritual Insight - Karki, Tej Bahadur; Khadka, Kalpana (Nepal Journal of Multidisciplinary Research, 2020)
Suicide is a social phenomenon and is mainly caused by mental disorder which may be attributed to by genetic, neurotic, and environmental constructs. A total of 5,124 people had committed suicide in the fiscal year 2016/17.The number rose to 5,317 in 2017/18 and to 5,785 in 2018/19. Various social and biological factors have significant roles to create the suicidal thought in depressed people. So it is necessary to explore the coping mechanism of suicidal thought. The main objective of this study is to explore the knowledge and practice for meditation, its process, therefore its effects on human mind and body to control the negative thought leading to suicide. The study is based on the review of literatures concerning a subject. The study has collected the various related literatures and thoroughly reviewed it. The result shows that there is significant effect of meditation on improving the psychological personalities just by reducing the stress level and controlling the suicidal feeling in mind. Many experimental studies have found the significant difference in pre and post thoughts of suicidal indicators after an intervention ina meditation program. In a modern society, people have no time to think for themselves, no time to connect with own inner qualities. The physical facilities are dominant on the daily life activities which has created problem in the work-life balance also so there is need to beware the people especially for many productive age groups to spend some time in doing regular meditation to improve the psychological personalities.